OUTCOME OF THE COMPRESSION DRESSING FOR TWO DAYS VS SEVEN DAYS AFTER VARICOSE VEIN SURGERY - Aamir Khan; Shehdost; Naima Shakeel; Ahmad Rafique (Journal of Ayub Medical College Abbottabad, 2023)
Background: Incompetence of the great saphenous vein (GSV) is a global issue and the most prevalent cause of chronic venous disease of leg. Clinical manifestations range from moderate to severe, including tiredness, heaviness, and irritation, as well as hyperpigmentation and leg ulcers. Significant advancements in GSV ablation employing percutaneous methods, such as endovenous laser ablation, have been made in recent years. (EVLA). Objective of the study is to compare the outcome of the compression dressing for two days vs. seven days after varicose vein surgery. This case control study was performed on the Surgical floor, Mayo Hospital, Lahore, from September 15 to March 15, 2020. Methods: We took a sum of 60 patients admitted from the outpatient department fulfilling the inclusion criteria after the approval of the ethical committee of the hospital. Group-A wore compression dressing for 2 days after surgery and Group-B wore compression dressing for seven days after surgery. Each patient received 1gm paracetamol I/V 8 hourly followed by tab. paracetamol 500mg P/O 8 hourly. Then the outcome of compression dressing was analyzed in form of mean postoperative pain. The mean pain score was assessed on 1 week. Data were entered in SSPS v23.0 and stratification of pain score was done against age, gender, and grades of varicose veins. A comparison of the two groups was done by applying a t-test. A p-value ‰¤of 0.05 was considered statistically significant. Results: We took a sum of 60 patients with Primary varicose veins based on their eligibility for this study. Patients were divided into two groups, i.e., Group-A (Compression dressing for 2 days) and Group-B (Compression dressing for 7 days). Average ages of patients in group A were 33.4±9.6 years and in the group, B was 35.4±9.9 years. A mean pain score of 4.5±1.2 was noted in patients in group-A (Compression dressing for 2 days) while 2.9±0.8 in patients in group B (Compression dressing for 7 days) with a p-value of 0.0001 which is statistically significant. Conclusion: When compression stockings are used for more than two days after the Trendelenburg’s procedure is done, it can lead to lesser pain and enhanced physical activity in the first week post operatively.